‘Umdah al-Muhtājīn: Rujukan Tarekat Syattariyah Nusantara - Damanhuri Damanhuri (Ulumuna, 2017)
This article explores the specification of ‘Umdah al-Muhtājīn, a monumental work in Shattariah Sufi order taught which was developed by the prominent Nusantara ulama Shaykh Abdurrauf as-Singkili. This study reveals a close relationship between Shattariah Sufi order in Indonesia and Abdurrauf, as the teacher and leader of this Sufi order, and between the work and Shattariyah Sufi order. It is revealed that the content of ‘Umdah al-Muhtājīn and specification of Syattariyah Sufi order have very common basic knowledge foundations. Therefore, before joining any Sufi order, one must have sufficient Islamic knowledge about Sufi and should learn its specific practices. The information on knowledge chain (sanad ilmu) and teacher chain in the practice of this Sufi order discloses that ‘Umdah is the basic guideline for followers and practices of Syattariyah Sufi order.